(untitled) (Journal of the College of Basic Education, 2026)
This study examines the language and meaning systems of English proverbs about love, with an emphasis on how differences in meaning enhance their persuasive impact and beauty. Love is a common feeling shared by people everywhere, but in stories and sayings, it is often described using phrases that do not mean exactly what they say. This is done to clearly express deep social and emotional ideas. The research focuses on the issue of insufficient semanticaly quantitative analysis of how particular linguistic features—such as metaphor, oxymoron, and hyperbole—operate to fulfill unique semantic roles within the category of love proverbs. The study has two main goals: first, to recognize and group the most common types of semantic deviations found in English love proverbs; and second, to analyze how these deviations are communicated to the audience. The procedure included a quantitative examination of a carefully selected dataset containing fourteen English proverbs. These data were collected from different dictionaries and literary works, selecting information that relates to a general understanding of love, such as romantic, family, and friendly feelings. Based on the analytical frameworks proposed by Leech (1969) and Gibbons and Whiteley (2018), the researcher classified the proverbs into six main categories: metaphor (which includes personification), simile, metonymy (which includes synecdoche), tautology, hyperbole, and oxymoron. The results show that these changes in meaning enable proverbs to move beyond their direct interpretations, offering a deeper way to understand and express the various aspects of love, including its complexities, conflicts, and strong emotions, making it easier for both the speaker and the listener to grasp and remember.